O prisioneiro de Érico Veríssimo : uma obra além das ideologias - Berthier, Jean Jacques Dutra (2008)
The gaucho writer Erico Verissimo had a period in his literary production which boarded with priority to questions sociopolitics of the comtemporarity. One of the works this period is The prisioner, in 1967. That novel is adapted in a country of the south west Asiatic that is sub intervention of a world potency. The presente work analyses the work The prisioner in which Erico Verissimo don t only make a novel of contation sociopolitic but presents a work against the war in which the human creature be restrict of his liberty. The personages or the the types of the work are symbolics, don t have names, being designated only by professional titles. His plot is in only 24 hours in a constant tension. The matter narrative of the novel enables to verify as the writer goes over there of a contestation politic of a war and his consequences. By to make a literature of realistic statute and the configuration of the personages representatives of the restrict libert individual and social, the novel The prisioner returns a way of the knowledge and understanding critical above the inhumanization and his consequences in that the person be priosioner to the Gear. Yet being a work markily politic The prisioner has a posture aparty that presents through his types, persons private save entirely, except in part private of his plenitude as social criature